If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 = c + -5 Reorder the terms: 3 + 2x = c + -5 Reorder the terms: 3 + 2x = -5 + c Solving 3 + 2x = -5 + c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = -5 + -3 + c Combine like terms: 3 + -3 = 0 0 + 2x = -5 + -3 + c 2x = -5 + -3 + c Combine like terms: -5 + -3 = -8 2x = -8 + c Divide each side by '2'. x = -4 + 0.5c Simplifying x = -4 + 0.5c
| =6-2x | | x^2-14x=17 | | 8n-7(-8-8n)=56 | | 5/6-16/21x-1/3-1/9x= | | 93.96=4.7p+8.7 | | 4xy+6x+2y+3=0 | | (4+g)(-11)=72 | | 6a^3b+9ab^4= | | log(5x+40)=3 | | -16t^2+8t+1= | | (N^12)^-1/6 | | h=-16t^2+8t+1 | | 6x+3+8x+11= | | (3.14)(6/2)6 | | m^2-4m=21 | | (8xy)+(15xy)= | | x^2+y^2-12x+4y=-15 | | 19.00+1.50x+15.00+2.75x= | | 20-15k=17 | | 3w+4= | | 4(x+-5)-5=6x+7.4-4x | | 10(x+5)=6x+6 | | 49x^2-84x+k= | | 4=-7+2n | | 50V*e^-t/T | | -9x-y=23 | | x^2+kx+36= | | r=cm+cn | | r=cm+cnform | | 8y+(y^2)=-16+4x-(x^2) | | 8-3y=128 | | (-5mn^3)(4m^2n^2)= |